Odpowiedzi

2009-11-04T18:26:31+01:00
A. = a-[a-1+a]= a-a+1-a=1-a
B.=-x-[-1+x-x+1]=-x
C.=x-[y-x+y-x-y+x]=x-(y-x)=x-y+x=2x-y
D.=1-a-(1-a+1-2a-1+3a)-a-1=1-a-1-a-1=-1-2a
Najlepsza Odpowiedź!
2009-11-04T18:27:58+01:00
A. a-[a-(1-a)]=a-[a-1+a]=a-2a+1=1-a
B. -x-[-(1-x)-(x-1)]=-x-[-1+x-x+1]=-x
C. x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]x-y+x=2x-y
D. 1-a-[1-(a-1)-2a-(1-3a)]-a-1=1-a-[1-a+1-2a-1+3a]-a-1=1-a-1-a-1=-2a-1
1 5 1
2009-11-04T18:27:49+01:00
A. a-(a-1+a) = a-a+1-a = -a +1
B. -x-(-1+x-x+1)=-x+1-x+x-1=-x
C. x-(y-x+y-x-y+x)=x-y+x-y+x+y-x=2x-y
D. 1-a-(1-a+1-2a-1+3a)-a-1=1-a-1+a-1+2a+1-3a-a-1=-1-2a